2015
DOI: 10.1016/j.landusepol.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting brownfield regeneration in post-socialist space: The case of the Czech Republic

Abstract: a b s t r a c tUsing an example of the Czech Republic, this explorative study attempts to answer the question of what factors have a significant influence on a successful regeneration of brownfields in a post-socialistic space. The study is based on a comparative analysis of two data files -the database of existing brownfields provided by the national CzechInvest agency, and the database of successfully regenerated brownfields compiled by the authors themselves. The paper consists of three interrelated parts, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 26 publications
0
54
0
1
Order By: Relevance
“…In the examined region, most of the remains of the previous industrial production is situated outside of the administrative center, and the region itself shows a more rural type of settlement. Osman et al (2015) identified an asymmetry in the investments into brownfields in rural areas and in cities in favor of larger settlements. These findings correspond partially to the results presented here, which, however, can only be applied to regenerated brownfields that have found a new use in agriculture.…”
Section: Resultsmentioning
confidence: 99%
“…In the examined region, most of the remains of the previous industrial production is situated outside of the administrative center, and the region itself shows a more rural type of settlement. Osman et al (2015) identified an asymmetry in the investments into brownfields in rural areas and in cities in favor of larger settlements. These findings correspond partially to the results presented here, which, however, can only be applied to regenerated brownfields that have found a new use in agriculture.…”
Section: Resultsmentioning
confidence: 99%
“…Bartke et al, 2016 andLimasset et al, 2018). The specifics of brownfield regeneration in the post-communist space are widely discussed by Osman et al (2015). Among other key aspects of brownfield regeneration belong existence of strong potential markets, long-term vision, strong branding, strong partnerships, integrated development, and getting infrastructure into place (Dixon et al, 2011).…”
Section: The Theoretical Framework Of the Studymentioning
confidence: 99%
“…The remediation even at a hazard defence level requires huge -often uncertain -investments. The regeneration process of military brownfields is often complicated by fact that military brownfields have on average a larger size in comparison to brownfields of other origins (Osman et al 2015). Cooperation of the different groups actors is very important for successfully redevelopment of all types of brownfields (Alexandrescu et al 2014(Alexandrescu et al , 2017 and it could be presupposed that this type of cooperation and networking among actors is also important both for protection of environment and biodiversity in the former MTAs and for post-military development projects that aim at improved socio-economic development of the region.…”
Section: General Characteristics Of Military Training Areas (Mtas)mentioning
confidence: 99%